2014
DOI: 10.1111/ans.12755
|View full text |Cite
|
Sign up to set email alerts
|

Does early radiography alter remanipulation rates in paediatric forearm fractures?

Abstract: The day 1 post-operative radiograph does not influence management, and cannot be justified given the further cost for hospitals, unnecessary radiation and additional time required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…2,7 Several studies have also suggested simple paediatric forearm fractures that are reduced and cast under fluoroscopy receive no clinical benefit from post-reduction radiographs, saving on both costs and the dose-dependent effects of cumulative radiation exposure. [14][15] In addition to fluoroscopic guidance, a variety of other interventions exist which may improve outcomes in closed reduction of forearm fractures. Ultrasound-guided closed reduction of forearm fractures has also been shown to have similar success rates.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Several studies have also suggested simple paediatric forearm fractures that are reduced and cast under fluoroscopy receive no clinical benefit from post-reduction radiographs, saving on both costs and the dose-dependent effects of cumulative radiation exposure. [14][15] In addition to fluoroscopic guidance, a variety of other interventions exist which may improve outcomes in closed reduction of forearm fractures. Ultrasound-guided closed reduction of forearm fractures has also been shown to have similar success rates.…”
Section: Discussionmentioning
confidence: 99%